ESTIMATION OF MONITORING SYSTEMS SURVIVABILITY OF INFORMATIVE SPACE - Казакова, Надія Феліксівна (Eastern-European Journal of Enterprise Technologies, 2012)
The method of estimation and increase of adaptiveness and authenticity of probabilistic model of estimation vitality of the system defence of encipherement at the decision of the special tasks of monitoring the informative space is offered.